Interchanging characteristic of plasma spray coating from superhydrophobic to hydrophilic under the applied electric field. (3rd October 2021) - Swain, B.; Pati, A. R.; Mohapatra, S. S.; Behera, A.
ABSTRACT: In the current work, by using NiTi plasma spray, superhydrophobic property is developed for compressor parts used in aerospace engine. The durability of the coating enhances in case of droplet impingement in cold condition (temperature = 25 °C). For the hot condition the aforesaid coating needs to become hydrophilic for the retention of high durability characteristic. The discussed switching is achieved by keeping the coating with in an influence of electric field. The results revealed that the surface roughness (12.4 µm) of the coating supports the attainment of superhydrophobic characteristic depicting contact and rolling angle of 164° ± 1.5 and 8° ± 1, respectively at normal condition. By applying electric field, the coating is converted to hydrophilic in hot condition noticed by impact mapping of droplets. Furthermore, it has been observed that the coated steel plate shows better efficiency as compared to uncoated steel plate under electric field.